2019
DOI: 10.7150/jca.28755
|View full text |Cite
|
Sign up to set email alerts
|

Radial probe endobronchial ultrasound assisted conventional transbronchial needle aspiration in the diagnosis of solitary peribronchial pulmonary lesion located in the segmental bronchi

Abstract: Background: The diagnosis of peribronchial pulmonary lesions located in the tertiary bronchi, also known as segmental bronchi, as well as, the 4th order and 5th order segmental bronchi is very difficult. Histopathological specimens cannot be easily obtained by endobronchial biopsies (EBBX) due to the patent but small segmental bronchial lumen. The aim of the present study was to evaluate the diagnostic accuracy and safety of the novel technique with radial probe endobronchial ultrasound (R-EBUS) assisted conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…EBUS is a good approach for visualizing lesions to guide the sample biopsy and EBUS-TBNA has been suggested to have a sensitivity around 0.9 and a specificity to 1.0 in lung cancer diagnosing and staging (9,10). Currently, REBUS has been developed as a novel technique to guide TBNA sampling (11). In this retrospective study, we aimed to evaluate the diagnostic rate and complications when using REBUS followed by TBNA in the evaluation of lesions located in the 3rd to 5th segmental bronchi, near the inner lung field on the CT image and outside the bronchus.…”
Section: Introductionmentioning
confidence: 99%
“…EBUS is a good approach for visualizing lesions to guide the sample biopsy and EBUS-TBNA has been suggested to have a sensitivity around 0.9 and a specificity to 1.0 in lung cancer diagnosing and staging (9,10). Currently, REBUS has been developed as a novel technique to guide TBNA sampling (11). In this retrospective study, we aimed to evaluate the diagnostic rate and complications when using REBUS followed by TBNA in the evaluation of lesions located in the 3rd to 5th segmental bronchi, near the inner lung field on the CT image and outside the bronchus.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to RB [4], FB is relatively easy to operate. It plays an increasing important role in clinical [[5], [6], [7], [8], [9]]. Currently, The flexible bronchoscopy can basically replace many previous operations once requiring rigid bronchoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Arimura et al reported a similar trial, performing transbronchial brushing and TBB, with diagnostic yields of 62.9%, 77.1%, and 80.0% for brushing, TBNA, and TBB, respectively [4]. Furthermore, Huang et al showed a novel TBNA technique for central targets arranged by EBUS survey to ensure the puncture location, resulting in 87.5% diagnostic yield [5]. However, all these trials were performed with conventional (thick) devices, without delivering a guide sheath into tumours, and TBB or TBNA was performed after EBUS.…”
Section: Discussionmentioning
confidence: 99%